Anisotropic Thermal Expansion in an Anionic Framework Showing Guest-Dependent Phases - Zhuo, Zhu; Huang, You-Gui; Walton, Krista S.; Sato, Osamu (Frontiers in Chemistry, 2020)
Crystalline materials generally show small positive thermal expansion along all three crystallographic axes because of increasing anharmonic vibrational amplitudes between bonded atoms or ions pairs on heating. In very rare cases, structural peculiarities may give rise to negative, anomalously large or zero thermal expansion behaviors, which remain poorly understood. Host–guest composites may exhibit such anomalous behavior if guest motions controllable. Here we report an anionic framework of helical nanotubes comprising three parallel helical chains. The anisotropic interaction between the guest and the framework, results in anisotropic thermal expansion in this framework. A series of detailed structural determination at 50 K intervals enable process visualization at the molecular level and the observed guest-dependent phases of the framework strongly support our proposed mechanism.